Soil chemistry influences the phytotoxicity of metal oxide nanoparticles. (2017) - Anderson, Anne; McLean, Joan; McManus, Paul; Britt, David
Nanoparticles (NPs) of ZnO and CuO are used in an array of different commercial products. NPs could be introduced into soils by contamination after production from distribution and use, especially from their end-of-life fate. Purposeful introduction to soils may occur in formulations as pesticides, because of their antimicrobial properties, and as fertilisers, to increase the loading of the essential metals Zn and Cu into plant tissues. Use as fertilisers must ensure that application rates do not lead to phytotoxicity. Dose-dependent phytotoxicity is seen in several crops including wheat, Triticum aestivum, when grown hydroponically or in sand. Phytotoxicity is evidenced in wheat by reduced growth and higher tissue loads of Cu or Zn than control plants. Soil properties, however, can mitigate phytotoxicity. Growth reduction in the wheat seedlings was not observed when an alkaline calcareous field soil with initial pH of 8.3 was amended with 300 mg Cu/kg soil from CuO NPs although metal loads increased in the shoots, paralleling observations with ZnO NPs. Phytotoxicity of both NPs was evident in acidic commercial field soils. The level of soluble metal released from the NPs in the aqueous phase varied with soil. Solubility was determined by the soil water pH and in part by the nature of the materials present in the plant root exudates. For example, a typical root exudate, citrate, at pH 5, dissolved more Cu from CuO NPs than did a suspension in water. These findings indicate that phytotoxicity of these metal oxide NPs in soils will vary with the properties of the soils. Consequently soil properties will influence how the NPs could be used as fertilisers.